Poverty Levels in the Developed World - David Jesuit; Timothy Smeeding (Luxembourg Income Study (LIS), 2002)
In this contribution, we discuss the major concepts and approaches adopted by researchers to assess how successfully different policy regimes cope with poverty alleviation. We also present the most recent figures available for 22 countries for a variety of indicators using the most comprehensive source of income data currently available. Finally, we caution researchers to pay close attention to issues of data quality and suggest areas where more research is particularly warranted.
Keywords: 330; Armut; Industrieländer